Study on Fault Optimization of Intermediate Joint of Power Cable. Issue 1 (1st April 2022) - He, Dajiang; Liu, Bohan; Wang, Zhenwu; Shu, You; Liu, Minghui
Abstract: Cable joints are often prone to failure due to loose contact, small contact area and increased contact resistance, resulting in obvious heating. In the existing cable emergency repair work, the cable joints of the original section of the cable and the access end are made on site. Due to the long production time, the emergency repair speed is reduced. Therefore, this paper studies the connection mode of the new cable joint to make the contact between conductors more sufficient and the contact resistance smaller, and designs a scheme of three-phase cable plug-in intermediate joint with high safety and simple installation; at the position of cable joint, three kinds of flexible conductive polymer materials suitable for joint connection are proposed to be used at the contact gap between conductor and conductor, conductor and conductor sleeve, so as to make close contact, reduce contact resistance and further reduce the incidence of cable joint failure.